2015
DOI: 10.2135/cropsci2014.06.0424
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Association Mapping of Aspergillus flavus and Aflatoxin Accumulation Resistance in Maize

Abstract: Contamination of maize (Zea mays L.) with aflatoxin, produced by the fungus Aspergillus flavus Link, has severe health and economic consequences. Efforts to reduce aflatoxin accumulation in maize have focused on identifying and selecting germplasm with natural host resistance factors, and several maize lines with significantly reduced aflatoxin accumulation have been identified. Past linkage mapping studies have identified quantitative trait loci (QTL) that consistently reduce aflatoxin levels in maize. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 47 publications
3
45
0
1
Order By: Relevance
“…For Gibberella ear rot resistance, QTLs were reported in bins 2.04, 2.06 and 2.08, 3.02, 3.04, 3.05, 3.06, 5.04, 5.05 and 5.06 in sources of resistance from Canada, Germany and Uganda (Liakat Ali et al 2005;Martin et al 2011Martin et al , 2012Tembo et al 2014). The same genome regions seem to be also important for Aspergillus ear rot resistance (Robertson-Hoyt et al 2007;Mideros et al 2014;Warburton et al 2015). The most important QTL mapped in bin 2.03.…”
Section: Discussionmentioning
confidence: 99%
“…For Gibberella ear rot resistance, QTLs were reported in bins 2.04, 2.06 and 2.08, 3.02, 3.04, 3.05, 3.06, 5.04, 5.05 and 5.06 in sources of resistance from Canada, Germany and Uganda (Liakat Ali et al 2005;Martin et al 2011Martin et al , 2012Tembo et al 2014). The same genome regions seem to be also important for Aspergillus ear rot resistance (Robertson-Hoyt et al 2007;Mideros et al 2014;Warburton et al 2015). The most important QTL mapped in bin 2.03.…”
Section: Discussionmentioning
confidence: 99%
“…Association mapping studies have been widely reported for foliar diseases (Kump et al, 2011; Poland et al, 2011; Gowda et al, 2015; Olukolu et al, 2016), ear rot diseases (Zila et al, 2014; Warburton et al, 2015; Han et al, 2018), flowering time, and plant architecture (Wallace et al, 2016) in maize. In this study, we applied a comprehensive GWAS for popping expansion using 165,089 SNPs markers in 183 inbred lines with 2 yr of trial data.…”
mentioning
confidence: 99%
“…Different methods have been used to identify QTL and genes related to resistance to maize diseases such as linkage mapping on biparental populations and association mapping on diverse populations (Warburton et al, 2015). This has contributed to the heterogeneity among published results.…”
Section: Meta-analysis Of Qtl Studies For Resistance To Fungi and Virmentioning
confidence: 99%